A study on the behavioral intention to volunteer in community service among university students at University of Science, Malaysia (USM) / Siti Hawa Jamaluddin and Nur Amira Syifa’ Azli - Jamaluddin, Siti Hawa; Azli, Nur Amira Syifa' (2018)
Volunteers’ shortages have become one of the major problems in the most countries in the world. The issues have raised concerns in Malaysia as Malaysia currently has 1.2 million university students, however, unfortunately there is a lack of recent study of the involvement of the university students in volunteerism. The study examines the level of behavioral intention to volunteer in community service among students in University of Science, Malaysia (USM). A cross sectional survey among students in University of Science, Malaysia (USM) was applied and used in this study. The numbers of questionnaire distributed were 597 completed questionnaires but only 385 questionnaires were returned and useable. The data obtained were analyzed and these following findings were found out. The relationships of attitudes, subjective norms and perceived behavioral control (PBC) and their level of behavioral intention to volunteer in community service that are the variables in Theory of Planned Behaviour (TPB) were further examined. All of these relationships were found to be significant. The levels of behavioral intention to volunteer in community service among USM students were at a high level. Even though the intention was at the high level, but the number of students that registered as member of Non-governmental organization (NGO) is still at low level.